2013
DOI: 10.1002/biof.1151
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of ginkgolide terpene lactones following acute consumption of Ginkgo biloba extract

Abstract: Urinary biomarkers of plant food supplement (PFS) exposure/ intake represent an accurate, non-subjective tool for determining PFS consumption in humans with applications ranging from epidemiology to subject compliance in clinical trials. Ginkgo biloba remains one of the worlds most popular PFS, yet few studies have investigated the uptake and metabolism of its primary unique bioactives: the terpene lactones. To this end, we conducted a dual-dose, acute crossover intervention using Ginkgo biloba supplements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…In addition, both gingkolide A and bilobalide formed stable formate adducts at m / z 453.1400 and 371.0984, respectively. These results agree with those of Dew et al [73] . Rutinose, the rutin glycoside, was detected as its deprotonated molecule [M-H] ¯ at m / z 325.1139, and was confirmed by the characteristic chloride adduct [M+Cl] ¯ and isotopic pattern [M+H( 37 Cl)] ¯ at m / z 361.0908 and 363.0878, respectively.…”
Section: Resultssupporting
confidence: 94%
“…In addition, both gingkolide A and bilobalide formed stable formate adducts at m / z 453.1400 and 371.0984, respectively. These results agree with those of Dew et al [73] . Rutinose, the rutin glycoside, was detected as its deprotonated molecule [M-H] ¯ at m / z 325.1139, and was confirmed by the characteristic chloride adduct [M+Cl] ¯ and isotopic pattern [M+H( 37 Cl)] ¯ at m / z 361.0908 and 363.0878, respectively.…”
Section: Resultssupporting
confidence: 94%
“…Up to now, flavones glycosides, terpene lactones and other chemical components have been separated from and identified in Ginkgo biloba extracts Dew et al, 2013). Previous studies have shown that ginkgolide A, ginkgolide B, ginkgolide C, ginkgolide J, and ginkgolide K all have neuroprotective effects and antioxidative properties, especially on neuron injuries induced by cerebral ischemia Qin et al, 2014;Ma et al, 2012a,b;Numa et al, 2007;Vitolo et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The urine sample was prepared according to Dew et al (2014). 20 It was thawed at room temperature immediately before extraction, placed in an ultrasonic water bath (5 min), then vortexed (30 s) to ensure homogeneity. The sample was extracted in triplicate.…”
Section: Detection Of Ginkgolides and Bilobalide In Urinementioning
confidence: 99%
“…The software Excalibur® Release 2.0 SR2 (Thermo Electron, San Jose, CA, USA) was used for integration. The analysis was performed according to Dew et al (2014), 20 Table 1. The autosampler and column oven temperatures were set at 8°C and 35°C, respectively, and the injection volume was 20 µL.…”
Section: Detection Of Ginkgolides and Bilobalide In Urinementioning
confidence: 99%
See 1 more Smart Citation